THE ROLE OF HINDU VALUES IN PUBLIC RELATIONS : A COMMUNICATION PERSPECTIVE ON RELIGIOUS ENGAGEMENT - Astuti Wijayanti; I Gusti Ayu Putri Trisnayanti; Ni Made Indiana (International Conference on Multidisciplinary Research Perspective, 2025)
This study explores the role of Hindu values in shaping public relations (PR) practices within religious and cultural contexts. Public relations, in its contemporary understanding, extends beyond institutional image building to encompass the preservation of cultural identity, the cultivation of public trust, and the promotion of social cohesion. Grounded in Hindu philosophical frameworks such as Tri Hita Karana (harmony with the divine, humanity, and nature), Tat Twam Asi (empathy and mutual respect), and Desa Kala Patra (contextual adaptability), this paper argues that Hindu values provide an ethical and sustainable foundation for communication strategies. Employing a conceptual approach through critical literature review and contextual case reflections, the paper highlights how Hindu-based Public Relations (PR) contributes to cultural sustainability and community development. Illustrative examples include the elevation of Nyepi as a global symbol of peace and environmental awareness, and the role of institutions such as Parisada Hindu Dharma Indonesia (PHDI) in advancing cultural diplomacy and interreligious dialogue. Furthermore, the discussion addresses challenges in the digital era, particularly regarding the risks of misinformation, secularization, and cultural commodification, alongside the opportunities offered by digital platforms for broader engagement. The findings demonstrate that the integration of Hindu values into PR practices enriches the discipline by embedding ethical, empathetic, and culturally resonant principles, thereby supporting the achievement of sustainable development goals (SDGs), specifically in the domains of cultural preservation and community development.